2004
DOI: 10.1196/annals.1319.005
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Megacity for Global Sustainability: The New York Metropolitan Region as an Urban Biosphere Reserve

Abstract: The UNESCO World Network of Biosphere Reserves (WNBR), while not originally conceived to include urban areas, was intended to include sites representing all significant ecosystems with the goal of support for sustainable development locally and globally. Drawing on the example of the New York Metropolitan Region (NYMR), which has a population of 21.4 million, it is argued here that the eventual inclusion of the largest of the world's cities in WNBR not only is within the logic of the biosphere reserve concept,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Finally, even in contexts where decision makers have access to relevant knowledge, it may take time before this has an effect on policy, public awareness and political action (LieberherrGardiol 2008 ;Niemelä et al 2010 , p. 3238). One study from New York Metropolitan Area suggested that the connection between science and policy was weak because the scientifi c view was considered just one of many stakeholders involved in decisions (Alfsen-Norodom et al 2004 ). Furthermore, while some see linking science and the views of stakeholders as offering potential for knowledge co-production (Bayá Laffi te 2009 ), there are signifi cant paradigm differences to be dealt with in mediating approaches to urban biodiversity and ecosystem service issues (e.g., Antrop 2001 ).…”
Section: Do We Have Enough Science To Reliably Inform Implementation?mentioning
confidence: 99%
“…Finally, even in contexts where decision makers have access to relevant knowledge, it may take time before this has an effect on policy, public awareness and political action (LieberherrGardiol 2008 ;Niemelä et al 2010 , p. 3238). One study from New York Metropolitan Area suggested that the connection between science and policy was weak because the scientifi c view was considered just one of many stakeholders involved in decisions (Alfsen-Norodom et al 2004 ). Furthermore, while some see linking science and the views of stakeholders as offering potential for knowledge co-production (Bayá Laffi te 2009 ), there are signifi cant paradigm differences to be dealt with in mediating approaches to urban biodiversity and ecosystem service issues (e.g., Antrop 2001 ).…”
Section: Do We Have Enough Science To Reliably Inform Implementation?mentioning
confidence: 99%
“…Furthermore, ecosystem services governance is extremely complex since the environmental agenda of cities is intertwined with a number of issues and competing priorities, as well as multiple temporal and spatial scales of ecosystem processes and their relation to multiple infl uencing and impacted actors (Sendstad 2012 ). Several studies indicate that public institutions have a lack of cooperation across departments or levels of authority, and have an inadequate capacity to handle diverse information and deal with change to respond to environmental problems (Alfsen-Norodom et al 2004 ;Blaine et al 2006 ;Andersson et al 2007 ;Ernstson et al 2010b ). Strategies and regulations tend typically to focus only on a few ecosystem services at the local scale (Ernstson et al 2010b ), assume stability in their supply (Asikainen and Jokinen 2009 ), and show a lack of provisions connecting urban consumers of ecosystem services and the people managing the services that the urban consumers depend on, originating from outside the city boundaries (Blaine et al 2006 ;Puppim de Oliveira et al 2011 ).…”
Section: Knowledge Gaps Related To Governancementioning
confidence: 99%
“…According to Adell (1999), peri-urban zones are dynamic, both spatially and structurally, Living Reviews in Landscape Research http://www.livingreviews.org/lrlr-2008-3 and form distinctive areas of agricultural and non-agricultural activity. Alfsen-Norodom defines the entire area around metropolitan areas as a separate "biosphere" -a concept to see a landscape with dense and less dense built-up areas and generally a hybrid land use as a entirely "new form of (dynamic) landscape", with its own biotopes, ecosystems and landscape dynamics (Alfsen-Norodom, 2004;Alfsen-Norodom et al, 2004). A typical "biosphere" related variable, carrying capacity can be useful as variable, to measure the semi-urban area, which can be seen as a heterogeneous mosaic of natural, production and agricultural ecosystems (Allen, 2003).…”
Section: The Dynamics Approach: Urban Sprawlmentioning
confidence: 99%